The test of basic Mechanics Conceptual Understanding (bMCU): using Rasch analysis to develop and evaluate an efficient multiple choice test on Newton's mechanics - Sarah I. Hofer; Ralph Schumacher; Herbert Rubin (SpringerOpen, 2017)
Abstract Background Valid assessment of the understanding of Newton's mechanics is highly relevant to both physics classrooms and research. Several tests have been developed. What remains missing, however, is an efficient and fair test of conceptual understanding that is adapted to the content taught to secondary school students and that can be validly applied as a pre- and posttest to reflect change. In this paper, we describe the development and evaluation of the test of basic Mechanics Conceptual Understanding (bMCU), which was designed to meet these requirements. Results In the context of test development, qualitative and quantitative methods, including Rasch analyses, were applied to more than 300 Swiss secondary school students. The final test's conformity to the Rasch model was confirmed with a sample of N = 141 students. We further ascertained the bMCU test's applicability as a change measure. Additionally, the criterion validity of the bMCU test was investigated in a sample of secondary school students (N = 66) and a sample of mechanical engineering students (N = 21). In both samples, the bMCU test was a useful predictor of actual student performance. Conclusions The bMCU test proved to enable fair, efficient, and simultaneously rigorous measurement of secondary school students' conceptual understanding of Newton's mechanics. This new instrument might fruitfully be used in both physics classrooms and educational research.